North American Agreement on Environmental Cooperation; [and], North American Agreement on Labour Co-operation : background information (Government of Canada OttawaCA, 1993)
Presents a press release, ministerial statements, trilateral summaries and highlights of the Labour and Environmental Agreements.
Text in english and French